2013
DOI: 10.4172/2155-6121.s3-004
|View full text |Cite
|
Sign up to set email alerts
|

Food Allergy

Abstract: Adverse reactions to food may be produced by several mechanisms and present a great diversity of symptoms, which may be reproducible or not reproducible (occasional adverse food reactions). The reproducible adverse food reactions to minimal or usual amounts of food are classified as hypersensitivity reactions, which may be derived from immune disorders (food allergies) or derived from non-immune conditions (food intolerance). Here, we review the clinical presentations of food allergies according to the underly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 80 publications
0
5
0
Order By: Relevance
“…Equally difficult to control is the avoidance of oral antigen ingestion. Food allergies may produce respiratory symptoms [35]. Additionally, several airborne allergens also crossreact with food proteins as in the case of mite-shrimp-insects or fruitpollen-latex syndromes [36][37][38] and it is not uncommon to diagnose shrimp or fruit allergies in patients with mite-associated or polleninduced allergic rhinitis.…”
Section: Discussionmentioning
confidence: 99%
“…Equally difficult to control is the avoidance of oral antigen ingestion. Food allergies may produce respiratory symptoms [35]. Additionally, several airborne allergens also crossreact with food proteins as in the case of mite-shrimp-insects or fruitpollen-latex syndromes [36][37][38] and it is not uncommon to diagnose shrimp or fruit allergies in patients with mite-associated or polleninduced allergic rhinitis.…”
Section: Discussionmentioning
confidence: 99%
“…Diagnosis of allergic diseases is performed upon a good clinical history ideally based on an appropriate selection of diagnostic tests that do not overburden the patients with financial issues. The skin allergic tests and the in vivo and ex vivo provocation tests play ideal role, but when there are inexpensive and painless techniques of equal sensitivity and specificity available to demonstrate specific hypersensitivity to airborne and/or food allergens [35,36]. Our findings suggest that total serum IgE and AEC are useful for screening sensitization and allergen-specific IgE a reliable tool when skin tests are not possible.…”
Section: Discussionmentioning
confidence: 82%
“…In regard to diagnosing food allergy, a food provocation test under double-blind placebo-controlled conditions is considered the gold standard. 13 We instead opted to perform a single-blind placebo-controlled challenge provocation test because we anticipated that our patient would experience oral swelling and severe pain after ingesting food containing MSG. Because we had previously confirmed that the placebo test using saline was negative, we decided that a single-blind design was our best option in terms of patient safety during the provocation test.…”
Section: Discussionmentioning
confidence: 99%